The Characteristic Performance of Fluidized bed Ion Exchange - Mohamed, Malik M.; Kaseer, Nahidh W.; Mahdi, Iman Haider (Nahrain University College of Engineering Journal, 2009)
The aim of this work is to study the characterization of ion exchange in important characteristics (i.e., breakthrough time and exchange capacity) by investigation the performance of cation exchange column subjected to makeup solution in term of three different parameter (i.e., bed depth 5-45cm, NaCl salt concentration100-2000 ppm and feed flow rate 9.5-26.5l/h). Two second order polynomial model are proposed with Box Wilson composite rotatable design. The experimental result had shown an efficient performance of using ion exchange column with strong acid cation exchange resin in fluidized mode operation which given maximum breakthrough time and higher exchange capacity means the rate of exchange is very rapid to completed the removing of all undesired ions at a condition of low bed depth, high NaCl concentration and high feed flow rate.